Cancellable biometric system based on linear combination of trigonometric functions with special application to forensic dental biometrics. (5th September 2019) - Banday, Mahroosh; Mir, Ajaz Hussain
Biometric templates in its original form are susceptible to attacks and irrevocable if compromised, and thus need to be protected. The proposed template protection approach based on a linear combination of trigonometric functions secures the dental templates stored in forensic records and also maintains the recognition performance of the identification system simultaneously. Furthermore, the security analysis of this non invertible transformation has been done by making many attempts to revert the transformed templates back to the original domain which proved effectual in maintaining the non-invertibility. The experimental results indicate that this approach is practical with a low EER of 2%. Moreover, this system has a high recognition rate of almost 98% and rank 1 identification rate of 93.33% for original as well as transformed dental templates and it is worth to mention that varying the key value does not degrade the system performance in case of template renewability.